ANALISIS DAMPAK ZAKAT DALAM MENDUKUNG SUSTAINABLE DEVELOPMENT GOALS (SDGS 4) PENDIDIKAN BERKUALITAS - Jihadi, Azri Awra (JSE: Jurnal Sharia Economica, 2026)
Zakat shows great potential as an instrument of wealth redistribution to support the achievement of Sustainable Development Goals (SDG 4), although its implementation still faces obstacles related to limited funds, suboptimal targeting, and variations in institutional capacity that contribute to unequal access to education. This study aims to analyze the impact of zakat on access, motivation, and quality of education for those who are entitled to receive zakat, and to formulate strategies to strengthen zakat management in education. By applying a descriptive qualitative approach, data were collected through in-depth interviews with Amil zakat, teachers, and beneficiaries at MA and STIE in Depok using a purposive sampling technique. The results revealed that zakat in education contributes to improving access to learning, motivation, discipline, and achievement of students and is managed through a long-term empowerment approach that is aligned with Human Capital Theory and Philanthropy Theory. The research recommendations emphasize the need to strengthen the results-based monitoring system, expand skills guidance and career guidance, and intensify cross-sector collaboration to create an inclusive education ecosystem that supports the sustainable achievement of SDG 4.